The role of low-carbohydrate, high-fat diet in modulating autophagy and endoplasmic reticulum stress in aortic endothelial dysfunction of metabolic syndrome animal model - Eldakhakhny, Basmah; Bima, Abdulhadi; Alamoudi, Aliaa A.; Alnami, Abrar; Abo-Elkhair, Salwa Mohamed; Sakr, Hussein; Almoghrabi, Yousef; Ghoneim, Fatma Mohamed; Nagib, Reham Mohamed; Elsamanoudy, Ayman (Frontiers in Nutrition, 2024)
Background: Endothelial dysfunction (ED) is induced by insulin resistance, mediated by endoplasmic reticulum (ER) stress and disturbed autophagy. This study investigates the protective role of a low-carbohydrate, high-fat (LCHF) diet on ED, ER stress, and autophagy dysregulation in an experimental animal model of metabolic syndrome. Methods: Forty male Sprague-Dawley rats were divided into four groups: a Control group (standard diet) and three Dexamethasone (DEX) treated groups. Group II continued the standard diet, Group III received an LCHF diet, and Group IV received a high-carbohydrate, low-fat (HCLF) diet. At the end of the experiment, aortic tissue samples were obtained and used for histological, immunohistochemical (Endothelin and PCNA, biochemical (MDA, TCA, NO, 8-OH-dG, and Nrf2/ARE protein) and molecular (Endothelin, eNOS, Nrf-2 α, p62, LC3, BECN-1, PINK1, CHOP, BNIP3, PCNA) analysis. Results: Oxidative stress, autophagy markers, and ED markers are increased in the metabolic syndrome group. LCHF diet mitigates the adverse effects of DEX on endothelial dysfunction and oxidative stress, as evidenced by reduced BMI, HOMA-IR, and improved histological and molecular parameters. Oxidative stress, autophagy dysregulation, and ER stress play crucial roles in the pathogenesis of insulin resistance-induced endothelial dysfunction. An LCHF diet offers protective benefits against insulin resistance and related comorbidities, including endothelial dysfunction. Accordingly, the current study aims to investigate the potential protective role of a low-carbohydrate, high-fat (LCHF) diet against developing endothelial dysfunction, endoplasmic reticulum stress, and autophagy dysregulation in an experimental animal model of drug-induced metabolic syndrome. Understanding these relationships may reveal novel dietary strategies to mitigate ER stress-related metabolic disorders.